TWIST interacts with β‐catenin signaling on osteosarcoma cell survival against cisplatin. Issue 6 (31st December 2012) - Wu, Jianhuang; Liao, Qiande; He, Hongbo; Zhong, Da; Yin, Ke
Abstract Both TWIST and Wnt/β‐catenin signaling reportedly play important roles in osteosarcoma development. In the present study, we explored the regulatory effect of TWIST on β‐catenin in osteosarcoma cells and assessed how the functional interaction between TWIST and β‐catenin would impact osteosarcoma cell survival against chemotherapy agent cisplatin. Overexpression and knockdown of TWIST were respectively performed in Saos‐2 and MG‐63 osteosarcoma cells. Overexpression of TWIST in Saos‐2 cells significantly decreased the soluble β‐catenin level, phosphorylation of glycogen synthase kinase‐3β (GSK‐3β) at serine 9, the mRNA level of β‐catenin signaling target genes, and cell survival against cisplatin, which was strengthened by knocking down β‐catenin. Knockdown of TWIST in MG‐63 cells significantly increased the soluble β‐catenin level, phosphorylation of GSK‐3β at serine 9, the mRNA level of β‐catenin signaling target genes, and cell survival against cisplatin, which was reversed by knocking down β‐catenin or phosphatidylinositol 3‐kinase (PI3K) inhibitor LY294002. In conclusion, we demonstrate that TWIST decreases osteosarcoma cell survival against cisplatin by decreasing the soluble β‐catenin level through a PI3K‐dependent manner. This study provides the first evidence of a functional link between TWIST and β‐catenin signaling in osteosarcoma cells, which adds fresh insights into the molecular mechanism of osteosarcoma development. © 2013 Wiley Periodicals, Inc.